Postpartum Suicide a Case Report - Atılmış, Ümit Ünüvar; Üzün, İbrahim; Taktak, Şafak; Boran, Tansev (The Bulletin of Legal Medicine, 2003)
A woman, 32 years old, was found dead due to falling from 4th floor The autopsy was performed in the Morgue Department of the Council of Forensic Medicine, Istanbul. The cause of death was reported as generalised trauma leading to thoracal and abdominal organ lacerations, major vessel lacerations, massive haemorrhage complicated with clavicula, crib, and extremity fractures. Scene investigation, clinical findings, medical history and autopsy findings were evaluated altogether and the manner of death was defined as suicide.Key words: Postpartum, suicide, autopsy
Keywords: postpartum; suicide; autopsy